The Strategies for Improving Lecturer Performance Through Servant Leadership, Organizational Climate, Knowledge Management, and Job Satisfaction - Ridwan Gunawan; Sri Setyaningsih; Lina Novita (Cita Konsultindo Research Center, 2024)
Strategies for Improving Lecturer Performance Through Servant Leadership, Organizational Climate, Knowledge Management, and Job SatisfactionAbstract Higher education in Indonesia must prepare high-quality and adaptive human resources in facing rapid and dynamic global changes. Lecturers play an important role in achieving this goal by effectively implementing the tri dharma of higher education. However, there are still many lecturers who still need to meet the established quality standards. The Indonesian Defence University (Unhan RI) faces challenges in achieving lecturer performance targets, including certification and education levels, which still need closer to the target. This study aims to understand the factors influencing lecturer performance and its integration with other aspects, such as leadership and organizational climate. This study uses a quantitative approach with a descriptive survey method to test the hypothesis regarding how servant leadership, organizational climate, and knowledge management affect lecturer performance through job satisfaction as an intervening variable. The data will be analyzed using path analysis and SITOREM. The study was conducted on lecturers at the Defense University in three locations. The study shows that Servant Leadership, Organizational Climate, Knowledge Management, and Job Satisfaction directly influence Lecturer Performance, with Servant Leadership and Organizational Climate also indirectly affecting Lecturer Performance through Job Satisfaction. To improve lecturer performance, it is necessary to strengthen weak indicators in various aspects with priority improvements starting from organizational management. The Rector of the Defense University is advised to strengthen servant leadership, organizational climate, and knowledge management, and improve job satisfaction supervision. In contrast, lecturers are advised to improve performance through cooperation and time utilization.